Métodos de controle aplicados na mitigação dos efeitos danosos provocados pelas vibrações resultantes do desmonte de rochas com uso de explosivos: uma revisão - Jucá Filho, Alberto Jaques Aragão (2022)
The blasting using explosives is the most used method currently in mining for rock fragmentation. However, only a small part of the energy released by the detonation is converted into useful energy for fragmentation, with the rest of the energy being dissipated to the environment in various ways, including vibration. The vibration transferred through the rocky massif can propagate over great distances, which can cause damage to the remaining rocky massif, the structures and inconvenience to residents who live in the vicinity of the mining projects, being one of the main causes of complaint by the population. Therefore, the present work aims to develop a review in the academic literature on the three main methods of monitoring and mitigating the effects of vibration caused by rock blasting using explosives, namely: Damping barriers, Limitation of maximum load by waiting and Overlapping fronts. The technique of damping barriers consists of creating artificial barriers, which by impedance contrast, retain the low frequency waves, which cause the greatest damage to buildings. Even with a significant increase in the price of blasting, the high reduction in vibration levels makes the technique very useful in controlling vibration levels. The technique of Limitation of the maximum load by waiting is the main method of vibration control, since it allows the control of the vibration levels just by modifying some parameters of the fire plane through the attenuation law that describes the behavior of the waves in the blasting area to adapt them to the regulatory standard. The technique of overlapping fronts consists in the determination of adequate delay times so that the seismic waves generated in the blast arrive in phase opposition in the structures to be protected. This technique has great value, when associated with simulation methods, in the determination of adequate delay times for superposition control and prediction of possible damage generated by superposition of waves.